Fibrin turnover and organization of pleural injury: Bench to bedside - Komissarov, A; Rahman, N; Lee, Y; Florova, G; Shetty, S; Idell, R; Ikebe, M; Das, K; Tucker, T; Idell, S (American Physiological Society, 2018)
Recent studies have shed new light on the role of the fibrinolytic system in the pathogenesis of pleural organization, including mechanisms by which the system regulates mesenchymal transition of mesothelial cells and how that process affects outcomes of pleural injury. The key contribution of plasminogen activator inhibitor-1 to the outcomes of pleural injury is now better understood as is its role in the regulation of intrapleural fibrinolytic therapy. In addition, mechanisms by which fibrinolysins are processed after intrapleural administration have now been elucidated, informing new candidate diagnostics and therapeutics for pleural loculation and failed drainage. The emergence of new potential interventional targets offers the potential for the development of new and more effective therapeutic candidates.